Analisis Faktor yang Berhubungan dengan Kejadian HIV pada Gay, Waria, dan Lelaki Seks Lelaki di Kota Gorontalo - Yadhi Armyantho Gani; Sirajuddien Bialangi; Nikmatisni Arsad (Research Review: Jurnal Ilmiah Multidisiplin, 2026)
Human Immunodeficiency Virus (HIV) attacks the immune system and may progress to AIDS if untreated. Globally, 40.8 million cases were recorded in 2024, while Indonesia reported 63,707 new cases the same year. Gorontalo Province recorded 1,360 cases in 2025, with 347 in Gorontalo City. This study aimed to analyze the relationship between sexual partners, condom use, HIV knowledge, and STI history with HIV incidence among the GWL group (Gay, Transgender, and MSM) in Gorontalo City. A quantitative cross-sectional design was employed with 78 respondents selected through purposive sampling. Data were collected via questionnaire and analyzed using chi-square test. Results showed significant relationships between sexual partners (p=0.046), condom use (p=0.020), and HIV knowledge (p=0.019) with HIV incidence, while STI history showed no significant relationship (p=0.252). It is concluded that risky sexual behavior and low HIV knowledge are the primary factors associated with HIV transmission among the GWL community in Gorontalo City.